Adoptive T cell therapy cures mice from active hemophagocytic lymphohistiocytosis (HLH). Issue 12 (24th October 2022) - Weißert, Kristoffer; Ammann, Sandra; Kögl, Tamara; Dettmer‐Monaco, Viviane; Schell, Christoph; Cathomen, Toni; Ehl, Stephan; Aichele, Peter
Abstract: Primary hemophagocytic lymphohistiocytosis (HLH) is a hyperinflammatory syndrome caused by impaired lymphocyte cytotoxicity. First‐line therapeutic regimens directed against activated immune cells or secreted cytokines show limited efficacy since they do not target the underlying immunological problem: defective lymphocyte cytotoxicity causing prolonged immune stimulation. A potential rescue strategy would be the adoptive transfer of ex vivo gene‐corrected autologous T cells. However, transfusion of cytotoxicity‐competent T cells under conditions of hyperinflammation may cause more harm than benefit. As a proof‐of‐concept for adoptive T cell therapy (ATCT) under hyperinflammatory conditions, we transferred syngeneic, cytotoxicity‐competent T cells into mice with virally triggered active primary HLH. ATCT with functional syngeneic trigger‐specific T cells cured Jinx mice from active HLH without life‐threatening side effects and protected Perforin ‐deficient mice from lethal HLH progression by reconstituting cytotoxicity. Cured mice were protected long‐term from HLH relapses. A threshold frequency of transferred T cells with functional differentiation was identified as a predictive biomarker for long‐term survival. This study is the first proof‐of‐concept for ATCT in active HLH. Synopsis: Primary hemophagocytic lymphohistiocytosis (HLH) is a life‐threatening syndrome characterized by hyperinflammation and caused by impaired lymphocyte cytotoxicity. We established adoptive immunotherapy in HLH animal models under conditions of hyperinflammation. Adoptive immunotherapy with virus‐specific T cells (ATCT) cured mice from virus‐triggered active primary HLH. ATCT was successful without life‐threatening side effects in two different primary HLH mouse models, in Jinx mice and Perforin‐deficient mice. Long‐term chimerism and "functional" differentiation of donor CD8 T cells in the recipients predicted therapeutic success of ATCT. Abstract : Primary hemophagocytic lymphohistiocytosis (HLH) is a life‐threatening syndrome characterized by hyperinflammation and caused by impaired lymphocyte cytotoxicity. We established adoptive immunotherapy in HLH animal models under conditions of hyperinflammation.